The enigma of xanthogranulomatous osteomyelitis: report of a rare case with review of literature - Gupta, Arushi; Ahmad, Nehal; Khan, Sabina; Mohroo, Rubeena; Kataria, Aneesha (International Journal of Research in Orthopaedics, 2025)
Xanthogranulomatous osteomyelitis (XO) is a rare chronic inflammatory condition histopathologically characterized by foamy macrophages, lymphocytes, plasma cells and fibrosis. It primarily affects organs like gallbladder and kidney but rarely involves bone. To date, only 21 cases of bone XO have been documented. XO mimics neoplastic bone lesions, creating diagnostic challenges necessitating a comprehensive approach that includes a thorough clinical history, detailed radiographic evaluation and definitive histopathologic examination. Hereby, we report a rare case of 25-year-old male presenting with pain, swelling and fever in the left forearm. Imaging revealed features suggestive of osteomyelitis and histopathological examination showed sheets of foamy macrophages, chronic inflammatory cells and fibrosis, thus clinching the diagnosis of XO. Through the case report we wish to highlight the importance of considering XO in the differential diagnosis of bone lesions so to avoid misdiagnosis of malignancy.